Theory of Sum Frequency Generation Spectroscopy - Morita, Akihiro (Lecture Notes in Chemistry,, 2018)
This book describes fundamental theory and recent advances of sum frequency generation (SFG) spectroscopy. SFG spectroscopy is widely used as a powerful tool of surface characterization, although theoretical interpretation of the obtained spectra has been a major bottleneck for most users. Recent advances in SFG theory have brought about a breakthrough in the analysis methods beyond conventional empirical ones, and molecular dynamics (MD) simulation of SFG spectroscopy allows for simultaneous understanding of observed spectra and interface structure in unprecedented detail. This book explains these recently understood theoretical aspects of SFG spectroscopy by the major developer of the theory. The theoretical topics are treated at basic levels for undergraduate students and are described in relation to computational chemistry, such as molecular modeling and MD simulation, toward close collaboration of SFG spectroscopy and computational chemistry in the near future.